(untitled) (Research, Society and Development, 2021)
Introduction: The buccal adipose body is a specialized mass composed of adipose tissue. It is a deep structure to the buccinator muscle, however in children this organ can be extruded into the oral cavity, characterizing a clinical entity called herniation of the buccal adipose body. The present study aims to report a case of prolapse of the oral fat pad after trauma. Case Report: Male participant, 6 months old, victim of a fall from his own height, admitted to the emergency service, presenting an injury in the oral cavity. There was no syncope and emesis after the trauma, without underlying pathologies, chronic use of medications or allergies. There were no bleeding or behavior changes. There was a prolapse of the buccal adipose body after 6 hours of blunt trauma. Physical examination showed preserved bone contours in the upper and middle third of the face, absence of crackling or edema in the nasal bones and absence of facial injuries. On intra-oral examination, a reddish-yellow lesion, similar to fat, was inserted into the right cheek mucosa, with a soft consistency. The adopted therapy was the excision of the fat pad under local anesthesia. Discussion: After 18 months of the procedure, the participant is without asymmetry and the mother reported that there were no complications during breastfeeding during this period. Conclusion: The present case corroborated with the literature in its clinical, etiological and demographic aspects, being treated through therapy already established in the literature, showing a good prognosis.